A CONCEPTUAL STUDY OF AYURVEDIC MANAGEMENT OF MUKHADUSHIKA W.S.R TO ACNE VULGARIS: A REVIEW - Sharma, *Monika; Sharma, Anita; Sani, Rashmi (International Journal of Ayurveda and Pharma Research, 2016)
Acne is a cutaneous pleomorphic disorder of the pilosebaceous unit involving abnormalities in sebum production and is characterized by both inflammatory (papules, pustules and nodules) and non-inflammatory (comedones, open and closed) lesions. Propionibacterium acnes and Staphylococcus epidermidis are common pus-forming microbes responsible for the development of various forms of, acne vulgaris. In Ayurveda it is described under the Mukhadushika or Yuvanapidika which is type of Kshudraroga. It is generally androgenic disease which is seen at puberty on both sexes. Today due to imbalanced life style (Apathy) and heavy pollution this problem increasing day by day. Guru Aahar, Madhya, Anidra, Upvas, Krodha, Santap, Savbhav are some causative factor of Mukhadushika. It is generally due to vitiation of Vata, Kapha and Rakta having Shalmali like eruption on face. In Ayurveda for the treatment of Mukhadushika (Kshudraroga) mainly two type of Chikitsa are described i.e. Shodhana chikitsa and Shamana chikitsa. As described by various Acharya the Shodhana chikitsa includes Vamana, Nasya and Shiravedha. The Shamana chikitsa includes various types of Lepa and Pralepa. Vamana Virechana, Nasya and Shira vedha will be beneficial along with some internal and external herbal, Mineral and herbominaral Ayurvedic drugs. In this review article, we tried to highlight Ayurvedic Management of Acne vulgaris (Mukhadushika) mentioned in Ayurveda with scientific justification.